The Correlation between Sleep Pattern and Mentruation cycle for Interns in RSUD Dr. Moewardi Surakarta - Deaneva, Almira Muthia; Hidayati, Rosalia Sri; Sumardiyono, . (Nexus Kedokteran Komunitas, 2015)
Background: Interns often have a poor sleep quality due to assignments, uncertain shift duty, and preparation for academical tasks. This poor sleep quality can impact organ system in our body, including metabolic system, endocrine, and immune system. One of the impact from poor sleep quality is menstruation cycle disorder. This study aimed to know the correlation between poor sleep quality and menstruation cycle for interns in RSUD Dr. Moewardi Surakarta. Methods: This study was observational analytic research with cross sectional approach. The subjects of this research were 40 female interns and conducted at RSUD Dr. Moewardi. The sampling method used was purposive sampling after selected based on inclusion and exclusion criteria of the study. The dependent variable in this study was menstruation cycle, while the independent variable was sleep quality. Research subjects completed (1) informed consent, (2) L-MMPI questionnaire to determine the honesty of respondents in filling out the questionnaire, (3) Pittsburgh Sleep Quality Index (PSQI), (4) menstruation cycle questionnaire. The data obtained was analyzed using SPSS 16 program with Chi-Square and Contingency Coefisien Results: The results using Chi square was X2= 4.912. Based on the data analysis with number of significance ? = 0.05 obtained value of p = 0.027 (p <0.05), whereas Contingency Coefisien correlation was 0.331. Conclusion: There is significant relationship and weak correlation about sleep quality and menstruation cycle for interns in RSUD Dr. Moewardi Surakarta. Keywords: menstruation cycle, sleep quality